Interpretation of Soil Water Content into Dryness Index: Implication for Forest Fire Management - Muh Taufik; Budi Indra Setiawan (Institut Pertanian Bogor (IPB University), 2012)
Forest fire research is very important for tropical regions as the current available models on forest fire predictions and control were developed based on studies conducted in dry sub-tropical forest areas. The use of dryness index (DI) based on actual soil water content for assessing fire danger in wetland ecosystem was proposed in this paper. The study site was located in South Sumatera, Indonesia and study was conducted from April 1 st 2009 to March 15 th 2011. Fire danger was categorized into 4 levels; low, medium, dry, and extreme with its margin level was determined based on soil water retention curve analysis. All DI categories occurred in 2009, however only 2 categories (low and medium) were observed in 2010 and 2011. DI reached its maximum intensity in September 2009 with an onset rate of 1.4 per day based on analysis of time intensity curve. Information of onset rate is importance for forest fire management such as for estimating when the extreme category would be reached. Therefore anticipation and prevention efforts might be prepared prior to reaching certain danger level. Information on DI might be useful for water management planning in forest plantation areas as many of them are located in wetland ecosystem.